The Stress Effect Towards PDRM Personnel: A Case Study on Health Problems and Job Satisfaction in Kedah - Mohamed Sazif, Mohamed Subri (2011)
There is limited empirical evidence focusing on police stress, and that which does exist poses interpretive difficulties; still, writers continue to claim that police work is either the most stressful occupation or is among the most stressful. When comparing police work to the stress associated with other occupations, the case for police stress may be overstated. In modern life police stress is a common problem in Royal Malaysian Police. The positive effects of stress affect towards PDRM personnel health and job satisfaction. As a result, police officer and rank file have their own stress perceptions and they develop different kinds of strategies in order to manage stressful situations. A study on health problem and job satisfaction in department of Kedah are associated with quality of work life was conducted through interviews and questionnaire assessment of four different department which is Crime Investigation Department (CID), General Duty (GD), Commercial Crime Department (CC), and Narcotics Department (Narc). Factors analyses of the nature of police stress revealed four hypotheses about health problem, job satisfaction, ranking, and monthly income. As predicted by a variable, there is positive relationship between police stress with health problem, job satisfaction, ranking, age, gender, and monthly income. Research methodology, data analysis and finding will explain more about the police stress in this research. Finally, discussion, limitation of the study, suggestion and conclusion also discussed.